Perencanaan Waktu dan Penjadwalan Pelaksanaan Proyek Pembangunan Rusun TNI di Minahasa Utara - Estrellita V. Y. Waney; Shella M Ruitan (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Project management is the process of systematically implementing management functions (controlling, controlling and coordinating) on a project by using existing resources effectively and efficiently so that project objectives can be achieved optimally. Success in achieving project goals must go through a project completion process that adheres to triple constraint, namely: according to specifications, time and predetermined costs. The time linkage in the implementation of building construction projects need serious attention to avoid project delays, so a special assessment is needed in the construction implementation process. Delays ini construction project can caused by errors in estimating the time planning stage, or various possibilities, such as improper management, problems with materials, labor, equipment, finances, and the environment that are not support so that project implementation is hampered This inevitably results in work delays. Project delays for the Contractor will result in a loss of time and cost, because the profits expected by the Contractor will be reduced, or even no profit will be made at all. Furthermore, this research with the title Project Implementation Time Planning on the Construction of the AD ZIDAM/XIII MDK Yonzipur 19/YKN 1A North Minahasa Flats was carried out with the following stages: volume calculation, unit price analysis and work duration calculation. Finally, the results of calculations using the Bar Chart method and the S curve found, that the implementation time of this project was 252 days (36 weeks).